Quantitative Immunohistochemistry to Measure Regional Expression of Nurr1 in the Brain and the Effect of the Nurr1 Heterozygous Genotype - Kummari, Evangel; Guo-Ross, Shirley X.; Partington, Heath S.; Nutter, Jennifer Makenzie; Eells, Jeffrey B. (Frontiers in Neuroanatomy, 2021)
The transcription factor Nurr1 is a member of the steroid hormone nuclear receptor superfamily. Ablation of Nurr1 expression arrests mesencephalic dopamine neuron differentiation while attenuation of Nurr1 in the subiculum and hippocampus impairs learning and memory. Additionally, reduced Nurr1 expression has been reported in patients with Parkinson’s disease and Alzheimer’s disease. In order to better understand the overall function of Nurr1 in the brain, quantitative immunohistochemistry was used to measure cellular Nurr1 protein expression, across Nurr1 immunoreactive neuronal populations. Additionally, neuronal Nurr1 expression levels were compared between different brain regions in wild-type mice (+/+) and Nurr1 heterozygous mice (+/-). Regional Nurr1 protein was also investigated at various time points after a seizure induced by pentylenetetrazol (PTZ). Nurr1 protein is expressed in various regions throughout the brain, however, a wide range of Nurr1 expression levels were observed among various neuronal populations. Neurons in the parietal and temporal cortex (secondary somatosensory, insular, auditory and temporal association cortex) had the highest relative Nurr1 expression (100%) followed closely by the claustrum/dorsal endopiriform cortex (85%) and then subiculum (76%). Lower Nurr1 protein levels were found in neurons in the substantia nigra pars compacta and ventral tegemental area (39%) followed by CA1 (25%) and CA3 (19%) of the hippocampus. Additionally, in the parietal and temporal cortex, two distinct populations of high and medium Nurr1 expressing neurons were observed. Comparisons between +/- and +/+ mice revealed Nurr1 protein was reduced in +/- mice by 27% in the parietal/temporal cortex, 49% in the claustrum/dorsal endopiriform cortex, 25% in the subiculum, 33% in substantia nigra pars compacta, 22% in ventral tegemental area, and 21% in CA1 region of the hippocampus. Based on these data, regional mechanisms appear to exist which can compensate for a loss of a Nurr1 allele. Following a single PTZ-induced seizure, Nurr1 protein in the dentate gyrus peaked around 2 h and returned to baseline by 8 h. Since altered Nurr1 expression has been implicated in neurologic disorders and Nurr1 agonists have showed protective effects, understanding regional protein expression of Nurr1, therefore, is necessary to understand how changes in Nurr1 expression can alter brain function.